2009
DOI: 10.1128/aem.02187-08
|View full text |Cite
|
Sign up to set email alerts
|

Poultry-Associated Salmonella enterica subsp. enterica Serovar 4,12:d:− Reveals High Clonality and a Distinct Pathogenicity Gene Repertoire

Abstract: A European baseline survey during the years 2005 and 2006 has revealed that the monophasic Salmonella enterica subsp. enterica serovar 4,12:d:؊ was, with a prevalence of 23.6%, the most frequently isolated serovar in German broiler flocks. In Denmark and the United Kingdom, its serovar prevalences were 15.15% and 2.8%, respectively. Although poultry is a major source of human salmonellosis, serovar 4,12:d:؊ is rarely isolated in humans (approximately 0.09% per year). Molecular typing studies using pulsed-field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 32 publications
2
35
0
Order By: Relevance
“…All of the isolates in this study display a full range of virulence-associated genes and normal growth characteristics (Crayford, Humphrey, & Wigley, unpublished data), suggesting they are capable of causing gastrointestinal disease in humans. This differs from serotype 4,12:d, a monophasic isolate associated with broiler chickens but not considered pathogenic to humans (Huehn et al, 2009). It is of some interest that strain S04327-09 was the least invasive and poorest colonizer of the chicken.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the isolates in this study display a full range of virulence-associated genes and normal growth characteristics (Crayford, Humphrey, & Wigley, unpublished data), suggesting they are capable of causing gastrointestinal disease in humans. This differs from serotype 4,12:d, a monophasic isolate associated with broiler chickens but not considered pathogenic to humans (Huehn et al, 2009). It is of some interest that strain S04327-09 was the least invasive and poorest colonizer of the chicken.…”
Section: Resultsmentioning
confidence: 99%
“…In the UK, DT193 has emerged as a major phage type in human infection with some 48% of human isolates in 2010 of the phage type, and around one-half of these monophasic variants (Hopkins et al, 2012), and are also increasingly found in meat and poultry products in the USA (USDA, 2012). Monophasic Salmonella serotypes are considered an emerging problem in poultry that has also been implicated as a source of human infection (Huehn et al, 2009;DEFRA, 2012). The two major DT193 monophasic variants serotype 4,12:i:-and serotype 4,5,12:i:-have recently been isolated for the first time from UK poultry farms, with 12 incidents in 2010 and 2011 indicating their emerging threat to poultry production (DEFRA, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For these typing methods and the macrorestriction PFGE XbaI typing published by García et al DNA microarray analysis. DNA microarray analysis was performed as previously described (20). A total of 263 gene-specific 57-to 60-mer oligonucleotides, previously designed using the Array Designer 4.1 program (Premier Biosoft, Palo Alto, CA) according to Salmonella sequences from GenBank database (http://www.ncbi.nlm.nih.gov/), were included.…”
Section: Methodsmentioning
confidence: 99%
“…Signal values were normalized in order to present each data point as presence or absence. "Uncertain" hybridization probe signals (cutoff values between 0.25 and 0.4) were verified by PCR amplification as previously described (20), and individual decisions were made for the presence or absence of each target.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was reported that the monophasic serovar 4,12: d,Ϫ, which is highly adapted to poultry and is very rarely associated with human disease, lacks the galactonate and lpf operons (25). These genetic regions are present in S. Typhimurium and S. Enteritidis, which are serovars frequently asso-VOL.…”
Section: Discussionmentioning
confidence: 99%